Phenotypic plasticity of drought tolerance in tomato (Solanum lycopersicum L.) landraces and hybrid cultivars in Benin, Africa - EZIN, VINCENT; Houessou, Felix; Bryla, David R.; Ahanchede, Adam (My University, 2019)
Drought is one of the most important abiotic stresses hampering crop productivity worldwide and is responsible for 20 percent of crop loss in Africa annually. Drought occurrence is likely to increase with climate change; therefore, the identification of drought resistance cultivars is an important tool in meeting food demands. New cultivars are needed that are tolerant to drought. The aim of the present study was to evaluate drought tolerance and its relation to vegetative, reproductive, and physiological characteristics of 20 tomato genotypes, including 14 local landraces, five hybrid cultivars, and a wild relative species (LA1579). The experiment was conducted at the International Institute of Tropical Agriculture in Benin, Africa. Each genotype was exposed to three treatments; a fully irrigated control, moderate drought (no water for 15 days during the vegetative stage and 7 days during the reproductive stage), and severe drought (no water for 21 days during the vegetative stage and 9 days during the reproductive stage). Plant height and leaf production were reduced by the initial episode of severe drought by 4-27% and 1-6%, respectively, but were unaffected in most genotypes by moderate drought. There was also no difference in leaf chlorophyll levels as a result of drought, but drought had a significant effect on leaf fluorescence in many genotypes. Diho and Dogbo landraces flowered first (57 days) and Tropimech hybrid flowered last (74 days). Both landraces and hybrids were equally affected by drought during flowering and fruit development. Heat was a limiting factor for some genotypes (LA1579) resulting in flower drop and yield loss by 100%. The landraces flowered earlier and more profusely than the hybrids but as a group both were equally affected by drought during flowering and fruit development. Some genotypes were also affected by heat, including LA1579, which aborted its flowers and produced no fruit in any treatment. Overall, two local landraces, Diho and Tovinklin, were most tolerant to drought amongst the genotypes and potentially could be used in breeding programs to improve drought tolerance in tomato.
Keywords: Solanum lycopersicum; drought tolerance; fluorescence; flowering; fruit development; leaf chlorophyll; yield